Nonlinear 3D Finite Element Model for Square Composite Columns Under Various Parameters - MAHMOOD, DARA; Rafiq, Serwan; Adbullah, Muhammed (Iraqi Journal of Civil Engineering, 2022)
Composite columns are frequently used in constructing high-rise structures because they can minimize the size of the building's columns while increasing the floor plan's usable space. This study aims to create a nonlinear 3D finite element model for square composite columns designed for solid and hollow columns with various multi-skin tubes subjected to loads at eccentricities of (30 and 60) mm, compressive strength, and mesh size using the ABAQUS software. The comparison was based on the experimental data of six references of composite columns. While the compressive strength of concrete increases, the stiffness of the composite column rise. The ratio of concrete compressive strength values for composite column increased by (0, 12.3, 17.8, and 26.7 percent) for (fc'=25, 31.96, 35, and 40) MPa, respectively. The results of the different mesh sizes (20, 40, and 60) mm are showing; The experimental results and the finite element solution developed using the (20 X20) mm element correspond well. The nonlinear finite element analysis method was used, and the finite element outputs results were confirmed to be in favorable agreement with the experimental data